Was there any magnesium? - G. N. Sukhodolova (Акушерство, гинекология и репродукция)
Open letter by Galina N. Sukhodolova, MD, Toxicologist, Dr Sci Med, Professor, Senior Researcher, Department of Acute Poisoning and Somatopsychiatric Disorders, Clinical and Research Institute for Emergency Medicine, Moscow, Russia; Professor, Department of Pediatric Anesthesiology and Intensive Care, Pirogov Russian National Research Medical University, Moscow, Russia; Chairman of the Association of Clinical Toxicologists of Russia. The open letter dedicated to the ongoing resonant case of Elina Sushkevich.